Determinants and strategies behind commercial airports' performance in general aviation. (June 2022) - Giovanelli, Lucia; Rotondo, Federico
Abstract: Although general aviation has become increasingly important for commercial airports to diversify aeronautical activities and improve overall performance, little empirical research has been devoted to the topic so far. Whereas other aspects of commercial airports' business (low-cost traffic, scheduled traffic, cargo, commercial revenue) have been widely investigated, to our knowledge this is the first research focusing on the conditions and strategies driving general aviation performance. This paper aims to examine the determinants of general aviation operations in commercial airports and the relationships between determinants and strategies developed by market leaders to gain a competitive advantage. An explanatory sequential mixed method was used. First, a panel data analysis was carried out on all the 44 Italian commercial airports that have operated general aviation flights over the period 2007–2018, to understand which variables have an effect on general aviation traffic. Second, a qualitative investigation was used to highlight how airport companies that have achieved success exploit these variables to outperform competitors. The combination of both quantitative and qualitative data, and the patterns observed across cases, led to the presentation of eight theoretical propositions, which were summarized in a preliminary model. Highlights: Some external variables affect general aviation operations. Market leaders develop ad hoc strategies and skills to gain a competitive advantage. Competitive strategies differ depending on the context. Skills differ depending on the context and the type of competitive advantage. General aviation contributes to recovering from the COVID-19 crisis.